Effect of Dayak Onion (Eleutherine bulbosa (Mill.) Urb.) on the Immune Response and Gene Expression of Nile Tilapia (Oreochromis niloticus) Infected with Aeromonas hydrophila - Arini Resti Fauzi; Munti Yuhana; Widanarni Widanarni; Mia Setiawati; Usamah Afiff (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Abstract